Gender Differences in Depression, Coping, Stigma, and Quality of Life in Patients of Vitiligo - Neena S. Sawant; Nakul A. Vanjari; Uday Khopkar (Hindawi Limited, 2019)
Though vitiligo is one of the psychodermatological disorders which do not cause direct physical impairment, it is cosmetically disfiguring leading to serious psychological problems in daily life. We undertook this research to study patients of vitiligo the prevalence of depression, coping, stigma, and quality of life and comparison of the same in both genders. Patients diagnosed clinically as having vitiligo by consultant dermatologist were enrolled after informed consent and ethics approval. 156 patients were screened, of which 100 satisfying criteria were taken up for the study. A semistructured proforma was designed to collect the necessary information with administration of Beck's depression inventory, participation scale, dermatology life quality index, and adjustment to chronic skin diseases questionnaire. Depression prevalence was 63.64% in females and 42.86% in males (p<0.0457); the total mean BDI scores were significant with females having higher scores than males (p<0.0083). No significant differences were seen on participation scale though 52% females felt stigmatized as compared to 45% males (p <0.5779). While almost 97% of our patients had impaired quality of life there was no significant difference in both genders on the total score (p<0.3547). Females had significantly higher faulty coping style than males with significant differences on all domains and total scores (p< 0.0094). There was a strong association of depression with faulty coping and stigma (p< 0.0001) in both genders. Also association of stigma with quality of life showed highly significant findings in both genders (p< 0.0001) on all the domains of DLQI. This study helps in early identification of psychological problems in vitiligo patients and planning their future course of management, hence improving the prognosis and quality of life.